2018
DOI: 10.1055/s-0038-1636532
|View full text |Cite
|
Sign up to set email alerts
|

Red Blood Cell Transfusions Affect Intestinal and Cerebral Oxygenation Differently in Preterm Infants with and without Subsequent Necrotizing Enterocolitis

Abstract: In preterm infants lower rSO, but not rSO, values during and after RBC transfusions are associated with TANEC. Lower rSO and rSO variabilities after RBC transfusions may represent a diminished capacity for vascular adaptation, possibly leading to TANEC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The majority (83%) of the 18 studies that reported on cerebral oxygenation during and after RBC transfusion found r c SO 2 to be higher during and after RBC transfusion compared to pretransfusion levels in anemic preterm infants (7,15,30,34,35,39,(41)(42)(43)(44)(45)(46)(47)(48)(49). Non-significant changes in cerebral oxygen saturation during and after RBC transfusions were observed in 3 studies (32,33,36).…”
Section: Anemia Rbc Transfusions and Cerebral Oxygenationmentioning
confidence: 98%
See 1 more Smart Citation
“…The majority (83%) of the 18 studies that reported on cerebral oxygenation during and after RBC transfusion found r c SO 2 to be higher during and after RBC transfusion compared to pretransfusion levels in anemic preterm infants (7,15,30,34,35,39,(41)(42)(43)(44)(45)(46)(47)(48)(49). Non-significant changes in cerebral oxygen saturation during and after RBC transfusions were observed in 3 studies (32,33,36).…”
Section: Anemia Rbc Transfusions and Cerebral Oxygenationmentioning
confidence: 98%
“…Another explanation is the increased fraction of adult Hb in comparison with before RBC transfusion, thus reducing the fraction of fetal Hb with a shift in dissociation curve (15). Possible explanations for not finding a significant difference in cerebral oxygenation during and after RBC transfusion in several reports, may relate to liberal transfusion thresholds (32), missing r c SO 2 data before RBC transfusions (36), or adequate cerebral autoregulation providing a constant CBF (33).…”
Section: Rbc Transfusions and Cerebral Oxygenationmentioning
confidence: 99%
“…Our study found that the higher the red blood cell counts, the higher recovery of sinus rhythm. The reason is that the higher red blood cell counts, the more higher ability to carry oxygen, [25] which is conducive to increasing the tissue oxygen supply, reducing the tissue ischemia and hypoxia. At present, related studies recommend the use of norepinephrine as a booster drug during CPR, [18] because it is more reliable and suitable to control.…”
Section: Discussionmentioning
confidence: 99%